2000
DOI: 10.1159/000016765
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Characterization of the Rabbit Mandibular Condyle following Experimental Induction of Anterior Disk Displacement

Abstract: Previous studies in our laboratory have shown that surgical induction of anterior disk displacement (ADD) in the rabbit craniomandibular joint (CMJ) leads to cellular and extracellular alterations consistent with osteoarthritis. Similar findings were also reported in human ADD as well as osteoarthritis of other joints. The purpose of this study was to further characterize these histopathological findings at the ultrastructural level. The right joint of 15 rabbits was exposed surgically and all discal attachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The study of Sharawy et al involving the rabbit TMJ has supported other studies claiming that anterior disc emplacement causes intracellular and extracellular changes of osteoarthritis (Sharawy et al, 2000). In this study they have split all the connections of the disc but the posterior ones and investigated the condyles with electron microscopy after 2 weeks.…”
Section: Discussionsupporting
confidence: 66%
“…The study of Sharawy et al involving the rabbit TMJ has supported other studies claiming that anterior disc emplacement causes intracellular and extracellular changes of osteoarthritis (Sharawy et al, 2000). In this study they have split all the connections of the disc but the posterior ones and investigated the condyles with electron microscopy after 2 weeks.…”
Section: Discussionsupporting
confidence: 66%
“…Potential adverse effects of abnormal, mostly anterior disc position undoubtedly have attracted the greatest interest of researchers. Recent evidence from experiments in rabbits (34)(35)(36) indicated that surgically induced disc displacement entails alterations of TMJ tissues, which are similar to those observed in osteoarthrosis. This has neither been confirmed by another study in animals (37), nor is it supported by the present findings suggesting that abnormal disc position plays a statistically significant role only, when it is accompanied by loss of molar support.…”
Section: Discussionmentioning
confidence: 83%
“…According to the previous studies in chondrocytes of rabbit mandibular condyles, apoptosis has been observed in the upper layer of ADD cartilage after surgery. 4,14 Wu et al 15 demonstrated that the production of pro-apoptotic proteins, bax, Fas, and caspase-8 increased in the chondrocytes following ADD. However, the underlying mechanisms are poorly understood.…”
Section: Discussionmentioning
confidence: 99%